2001
DOI: 10.1002/1099-0682(200111)2001:11<2743::aid-ejic2743>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

[1H, 15N] NMR Studies of the Platination of Phosphorothioate Nucleotides − Monofunctional Sulfur Adducts versus Macrochelation

Abstract: cis‐[PtI2(15NH3)2] reacts rapidly with guanosine‐5′‐O‐(2‐thiodiphosphate) (GDP‐β‐S) to form a macrochelate in which Pt bridges the phosphorothioate S and guanine N7 atoms. Phosphorothioate(α‐S)‐containing self‐complementary decamer oligonucleotides give rise to relatively long lived S‐bound monofunctional adducts, the fate of which is sequence dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Comparison of this reaction profile with the outcome from that of the reaction between I and the phosphorothioate substituted dimer R,S-d(GsG) (IIs) indicated close similarity to the previous report [14] in which the main product was an N,S-macrochelate formed through linkage of the platinum centre to both the phosphorothioate sulphur ( 15 Figure 1(b)). Although forming the main product, as indicated by the intensity of the cross-peaks in the 2D [ 1 H, 15 N] HSQC NMR data, some formation of an N7, N7 cross-link also occurred, although to a much lesser extent, as indicated by the presence of cross-peaks at the same chemical shifts as those for 3 and 4 in Figure 1( [25] and in line with previous findings [14]. Thus, as an isolated structural element, it is clear that sufficient reactivity and structural flexibility exists in the dimer d(GsG), IIs, to form the S,N macrochelate in the same manner as that reported previously for the self-complementary duplex ODN R,S-5d(TATGsGCCATA) 2 -3 .…”
Section: Reactions With D(gpg) and Rs-d(gsg)supporting
confidence: 86%
See 3 more Smart Citations
“…Comparison of this reaction profile with the outcome from that of the reaction between I and the phosphorothioate substituted dimer R,S-d(GsG) (IIs) indicated close similarity to the previous report [14] in which the main product was an N,S-macrochelate formed through linkage of the platinum centre to both the phosphorothioate sulphur ( 15 Figure 1(b)). Although forming the main product, as indicated by the intensity of the cross-peaks in the 2D [ 1 H, 15 N] HSQC NMR data, some formation of an N7, N7 cross-link also occurred, although to a much lesser extent, as indicated by the presence of cross-peaks at the same chemical shifts as those for 3 and 4 in Figure 1( [25] and in line with previous findings [14]. Thus, as an isolated structural element, it is clear that sufficient reactivity and structural flexibility exists in the dimer d(GsG), IIs, to form the S,N macrochelate in the same manner as that reported previously for the self-complementary duplex ODN R,S-5d(TATGsGCCATA) 2 -3 .…”
Section: Reactions With D(gpg) and Rs-d(gsg)supporting
confidence: 86%
“…The presence of a 15 N spin-label within the inorganic complex allows reactions to be elegantly monitored by means of 2D [ 1 H, 15 N] HSQC NMR spectroscopy according to tried and tested principles. Formerly, it was shown that macrochelate formation occurred in the form of cis-[Pt(NH 3 ) 2 (GDP-β-S)-N7,S] in which Pt was bound to the N7 and S centres of a macrochelate [14]. Reactions with model ODNs were also monitored in a similar way, and speculation was made concerning the nature of the products formed.…”
Section: International Journal Of Inorganic Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the kinetically inert Pt( II ) yields, in the form of chloro(diethylenetriamine)platinum( II ) chloride, by reaction with AMPS exclusively a (phosphorothioate)platinum( II ) complex 21. In accord herewith, cis ‐(NH 3 ) 2 PtI 2 forms with guanosine 5′‐ O ‐(2‐thiodiphosphate) (GDP‐β‐S) a macrochelate in which Pt( II ) bridges the phosphorothioate S and guanine N7 atoms 22. There is also a study23 of p ‐nitrophenyl thiophosphate in which the effects of Mg 2+ and Cd 2+ on the rate of hydrolysis of this ester are compared.…”
Section: Introductionmentioning
confidence: 78%